Simbolisme Ritual, Pengalaman K Analisis Simbolisme Ritual dan Pengalaman Keagamaan dalam Kerangka 'Sacred Canopy' di Gereja Masehi Advent Hari Ketujuh Kayu Putih, Jakarta Timur - Kamila Rahma Shalehah, Kamila Rahma Shalehah (DIALEKTIKA, 2024)
Starting from its uniqueness, the Adventist Church is known for its strong symbolism in its religious practices. Joachim Wach's phenomenological approach is integrated with Rudolf Otto's Numinous theory and Peter L. Berger's Sacred Canopy theory, which emphasizes the importance of understanding the subjective experiences of congregation members. This research can provide insights into the interaction between ritual symbolism and broader religious experiences in giving meaning to human life within the framework of the "sacred canopy." This research uses a Descriptive-Analytical Qualitative method with data collection techniques based on primary data from observations, direct interviews with 7 informants, and documentary studies. Secondary data were obtained through literature studies, and the purpose of this research is to understand the concept, analyze the essence, and forms of the congregation's religious experience through the lens of the Sacred Canopy. The research results show that religious practices at Kayu Putih Seventh-day Adventist Church are not merely religious activities, but rather a complex process involving the construction of social reality through symbolic interactions between individuals and their community as well as their surrounding environment. The concept of the sacred canopy developed by Joachim Wach, which includes dimensions of religious experience and practice, is highly relevant in maintaining a coherent religious social reality that provides meaning and a sense of security for the members of Kayu Putih Seventh-day Adventist Church.